2012
DOI: 10.1038/onc.2012.574
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 inhibits the growth, invasion, metastasis and angiogenesis of neuroblastoma cells through targeting hypoxia-inducible factor 2 alpha

Abstract: Recent evidence shows that hypoxia-inducible factor 2 alpha (HIF-2α) may have critical roles in the growth and progression of neuroblastoma (NB) under non-hypoxic conditions. However, the underlying mechanisms and clinical potentials of normoxic HIF-2α expression in NB still remain largely unknown. In this study, HIF-2α immunostaining was identified in 26/42 NB tissues, which was correlated with clinicopathological features. In subtotal 20 NB cases, microRNA-145 (miR-145) was downregulated and inversely correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 38 publications
3
151
0
Order By: Relevance
“…It has been reported that miR-145 is expressed at low levels in breast cancer, colon cancer, lung cancer and other tumor tissues compared with normal tissues (14). As previously demonstrated, by transfecting synthetic miR-145 oligonucleotides into neuroblastoma cells, endometrial stem cells, and bladder cancer cells, the expression of genes, such as insulin-like growth factor receptor I (IGF-IR) and hypoxia-inducible factor 2α (HIF-2α) was downregulated, which resulted in the inhibition of cancer cell growth and invasion (15)(16)(17).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that miR-145 is expressed at low levels in breast cancer, colon cancer, lung cancer and other tumor tissues compared with normal tissues (14). As previously demonstrated, by transfecting synthetic miR-145 oligonucleotides into neuroblastoma cells, endometrial stem cells, and bladder cancer cells, the expression of genes, such as insulin-like growth factor receptor I (IGF-IR) and hypoxia-inducible factor 2α (HIF-2α) was downregulated, which resulted in the inhibition of cancer cell growth and invasion (15)(16)(17).…”
Section: Introductionmentioning
confidence: 89%
“…It was found that miR-145 had the lowest expression level in the HepG2 cells compared with the other cancer cells. miR-145 as a tumor suppressor, has been shown to inhibit cancer cell growth by targeting c-Myc and p53 in colon and breast cancers (30), IGF-IR in human bladder cancer (17) and HIF-2α in neuroblastoma (15). In our study, our results indicated that miR-145 reduced the mRNA expression of CDK6, cyclinD1, c-Myc and Sp1 in the HepG2 cells, thus indicating that the inhibitory effects of miR-145 on HepG2 cell proliferation may occur through the regulation of the cell cycleassociated genes, which results in anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…to be an upstream cause for the overexpression of HIF-2α in adrenal neuroblastoma as forced expression of miR-145 reduces HIF-2α protein level and suppresses tumor growth, invasion, angiogenesis and metastasis (Zhang et al 2014). Collectively, these findings indicate that HIF-2α but not HIF-1α contributes to the pathogenesis of neuroblastoma and related endocrine disorder syndromes.…”
Section: :1mentioning
confidence: 67%